Educação e neoliberalismo: o dilema da escola privada frente ao processo de mercantilização do ensino - Giachini, Joice Marizete (Universidade do Vale do Rio dos Sinos, 2020)
The aim of this study was about to analyze problems which has added to the process of management of private Catholic Schools as a result of neoliberal ideologies that promote commodification of teaching. The adopted methodology was qualitative imprint and data gathering subsidized by means of essay of a diary of field; construction of a SWOT matrix; bibliographic research; and a questionaire headed to group of parentes and/or students legal responsable of school which served as locus of research. The main conclusion reached with the research was that Catholic School needs to improve the way with which communicates its institutional identity. Being adapted to comercial imprint strategies is a necessary action to its financial survival, however, its charismatic profile and the importance of its pedagogical Project have been overshadowed by such pratices. Interventional measures so that the “balance” between financial and charismatic identity be equated and balanced are highly necessary.
Keywords: Neoliberalismo; Educação confessional católica; Gestão educacional; Educação básica; Catholic confessional education; Educational management; Basic education; ACCNPQ::Ciências Humanas::Educação